Duo luo tian shi = Fallen angels [videorecording (DVD)] / a Jet Tone Production ; directed by Wong Kar-wai ; producer, Jeff Lau ; script writer, Wong Kar Wai. - Wong, Kar-wai, 1958-; Wong, Kar-wai, 1958-; Wong, Kar-wai, 1958-; Liu, Zhenwei; Lai, Leon, 1966-; Reis, Michele; Kaneshiro, Takeshi; Yeung, Charlie, 1974-; Mok, Karen (Kino on Video, 2004)
In the garishly lit late-night world of Hong Kong, the lives of four lonely people briefly intersect: Wong Chi-Ming, a jaded hit man who wants out of his dangerous, solitary business but is leery of emotional involvement; the Agent, the beautiful partner-in-crime he's never met, but who's fallen in love with Chi-Ming anyway; Baby, a bleached-blonde, nightcrawling cookie who's looking for love but will settle for being remembered by Chi-Ming; and He Zhiwu, a mute, overgrown child who, in the wee hours, breaks into closed-up shops, opens them for business and forces customers to shop against their will.